Portrait of Indonesian Workers Life in Saudi Arabia in the Novel Kedai 1001 Mimpi by Valiant Budi - Tri Pujiati; Sri Marsita (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
A grim portrait of life is often shown by migrant workers who work in Saudi Arabia through novel Kedai 1001 Mimpi by Valiant Budi, researcher tries to peel the grim portrait of migrant workers in Saudi Arabia. This research, using qualitative descriptive method and literature sociology approach, seeks to explore the portrait of humanity accepted by Indonesian labor migrants working in Saudi Arabia. The results of this study show a portrait of humanity experienced by female and male migrant workers. The portrait of life that happens to women in the novel Kedai 1001 Mimpi by Valian Budi is sexual harassment, physical violence, accusation, lack of protection. The portrait of humanity portrayed in male migrant workers is harassment, dissension, defamation, and unclear employment contracts. This research has significance in the humanitarian and social fields that there are many grim portraits of living witnesses who have worked as migrant workers in Saudi Arabia so that the government needs to find the right solution so that the forms of injustice received by migrant workers in Saudi Arabia do not recur.